Table of Indefinite Integrals
Table of Indefinite Integrals
Table of Indefinite Integrals
xn+1
Z
Z 1 (a) xn dx = +C
(1) (a) xn dx n+1
1 1 ax
Z Z
Z (b) eax dx = eax d(ax) = e +C
(b) eax
dx a a
1
Z Z Z Z
(c) ln x dx = 1 · ln x dx = x ln x − x dx = x ln x − dx = x ln x − x + C
x
Z
(c) ln x dx
1 1
Z p Z Z
Z 1 1
(2) 2 (a) x x2 + 1 dx = (x2 + 1) 2 d(x2 ) = (x2 + 1) 2 d(x2 + 1)
p
(a) x x2 + 1 dx 2 2
3
1 2(x2 + 1) 2 1 3
Z · + C = (x2 + 1) 2 + C
=
(b) x
p
4 − x2 dx 2 3 3
1 1
Z p Z Z
1 1
(b) x 4 − x2 dx = (4 − x2 ) 2 d(x2 ) = − (4 − x2 ) 2 d(4 − x2 )
Z
x 2 2
(c) √ dx 3
4 − x2 1 2(4 − x2 ) 2 1 3
=− · + C = − (4 − x2 ) 2 + C
2 3 3
Z 1
(3) x 1 1 (4 − x2 ) 2
Z Z
(a) xex dx (c) √ dx = −
1
(4 − x2 )− 2 d(4 − x2 ) = − ·
1
+ C = −(4 − x2 ) 2 + C
4 − x2 2 2 1/2
Z
(b) x2 ex dx
Z Z
Z 3 (a) xex dx = xex − 1 · ex dx = xex − ex + C
2 2x3
(c) x e dx
Z Z Z
(b) x2 ex dx = x2 ex − 2xex dx = x2 ex − 2 xex dx = x2 ex − 2(xex − ex ) + C
Z Z
(4) (a) cos nθ dθ and sin nθ dθ = (x2 − 2x + 2)ex + C
1 1 1 1 2x3
Z Z Z
3 3 3
(c) x2 e2x dx = e2x d(x3 ) = · e2x d(2x3 ) = e +C
3 3 2 6
Z Z
(b) cos2 nθ dθ and sin2 nθ dθ
Z Z
(1 + cos nθ)2 dθ (1 + sin nθ)2 dθ 1 1
Z Z
(c) and 4 (a) (i) cos nθ dθ = cos nθ d(nθ) = sin nθ + C
n n
1 1
Z Z
Z Z
(5) (ii) sin nθ dθ = sin nθ d(nθ) = − cos nθ + C
(a) sin2 nθ cos nθ dθ and cos2 nθ sin nθ dθ n n
1 1
Z Z (b) Note that cos2 θ = (1 + cos 2θ), sin2 θ = (1 − cos 2θ)
(b) cos3 nθ dθ and sin3 nθ dθ 2 2
1 1 1
Z Z
(i) cos2 nθ dθ = (1 + cos 2nθ) dθ = θ+ sin 2nθ + C
2 2 2n
Z Z
(c) cos4 nθ dθ and sin4 n dθ.
1 1 1
Z Z
(ii) sin2 nθ dθ = (1 − cos 2nθ) dθ = θ− sin 2nθ + C
2 2 2n
–1– –2–
(c) (i) Z Z (c) (i) Note that
2 2
(1 + cos nθ) dθ = (1 + 2 cos nθ + cos nθ) dθ
cos4 nθ = cos2 nθ · cos2 nθ
1 1
Z Z Z
= dθ + 2 cos nθ dθ + cos2 nθ dθ = (1 + cos 2nθ) · (1 + cos 2nθ)
2 2
2 1
1
1
=θ+ sin nθ + θ+ sin 2nθ + C = (1 + 2 cos 2nθ + cos2 2nθ)
n 2 2n 4
1 1
(from 4a(i)) (from 4b(i)) = 1 + 2 cos 2nθ + (1 + cos 4nθ)
4 2
3 2 1
= θ + sin nθ + sin 2nθ + C
1 3 1
2 n 4n = + 2 cos 2nθ + cos 4nθ
4 2 2
Z
1 3 1
Z
∴ cos4 nθ dθ = + 2 cos 2nθ + cos 4nθ dθ
4 2 2
(ii)
1 3 2 1 1
Z Z
(1 + sin nθ)2 dθ = (1 + 2 sin nθ + sin2 nθ) dθ = θ+ sin 2nθ + · sin 4nθ + C
4 2 2n 2 4n
2 1 1 1 3 1 1
=θ− cos nθ + θ− sin 2nθ + C = θ + sin 2nθ + sin 4nθ + C
n 2 2n 4 2 n 8n
(from 4a(ii)) (from 4b(ii))
3 2 1
= θ − cos nθ − sin 2nθ + C (ii) Note that
2 n 4n
sin4 nθ = sin2 nθ · sin2 nθ
1 1
= (1 − cos 2nθ) · (1 − cos 2nθ)
2 2
1
= (1 − 2 cos 2nθ + cos2 2nθ)
1 1 sin3 nθ 1 4
Z Z
5 (a)
(i) sin2 nθ cos nθ dθ = sin2 nθ d(sin nθ) = · +C = sin3 nθ + C
n n 3 3n
1 1
= 1 − 2 cos 2nθ + (1 + cos 4nθ)
4 2
1 1 cos3 nθ 1
Z Z
(ii) cos2 nθ sin nθ dθ = − cos2 nθ d(cos nθ) = − +C = − cos3 nθ+C 1 3 1
n n
·
3 3n = − 2 cos 2nθ + cos 4nθ
4 2 2
Z
1 3 1
Z
∴ sin4 nθ dθ = − 2 cos 2nθ + cos 4nθ dθ
4 2 2
(b) (i)
1 1 1 3 2 1 1
Z Z Z
cos3 nθ dθ = cos2 nθ d(sin nθ) = (1 − sin2 nθ) d(sin nθ) = θ− sin 2nθ + · sin 4nθ + C
n n 4 2 2n 2 4n
sin3 nθ 1 3 1 1
1
= sin nθ − +C = θ − sin 2nθ + sin 4nθ + C
n 3 4 2 n 8n
(ii)
1 1
Z Z Z
sin3 nθ dθ = − sin2 nθ d(cos nθ) = − (1 − cos2 nθ) d(cos nθ)
n n
cos3 nθ
1
=− cos nθ − +C
n 3
–3– –4–